Catalogue of vesicular-arbuscular mycorrhiza strains - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
The Catalogue of vesicular-arbuscular mycorrhiza strains and results of evaluations of some this strains carried out from 1982-1985.